11 Clinical pathways and cascade effects in patients after thyroid ultrasound early in the evaluation of suspected thyroid disorders. An analysis of german health insurance data. (4th December 2019) - Hueber, Susann; Tomandl, Johanna; Hafner, Lucas; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Kühlein, Thomas
Abstract : Objectives: Thyroid disorders may cause many non-specific symptoms. In the evaluation of suspected thyroid disorder mostly only thyroid stimulating hormone (TSH) measurement is necessary. As thyroid ultrasound is readily available in German ambulatory care it is frequently used early in the diagnostic process without indication. This might be a trigger for cascades of further overdiagnosis and finally overtreatment. Cascades being defined as chains of diagnostic events and treatment that are difficult to influence once they have been started. In this study we aimed to describe clinical pathways of different groups with suspected thyroid disorder. We wanted to learn about the triggers of cascades, the drivers of diagnostic control loops and the final outcomes. Method: Routine data of patients with statutory health insurance held by the Bavarian Association of Statutory Health Insurance Physicians were used for retrospective analysis. Early use of sonography was defined as having an initial TSH test followed by a sonography within 28 days. Data of these patients were clustered in groups with regard to medical procedures. Clusters were then compared to identify factors related to medical overuse and overtreatment. Results: The sample included 58, 114 patients. Data analysis is not completed yet. The study design, the project status as well as the results, will be available until the conference and presented there. Conclusions: The early use of sonography in the evaluation of suspected thyroid disorders might trigger cascades of overdiagnosis and finally unnecessary surgical interventions. By systematically analyzing clinical pathways, we hope to contribute to the identification and reduction of overdiagnosis and overtreatment. The project is embedded in the PRO PRICARE health services research network (Preventing Overdiagnosis in PRImary CARE). PRO PRICARE is funded by the German Ministry of Research and Education.